Determinants of foreign investments in residential properties: evidence from Malaysian states - Gholipour, Hassan Fereidouni (International Journal of Strategic Property Management, 2013)
The last decade has witnessed a strong growth in foreign investments in residential properties (FIRP) in Malaysia. However, FIRP is not equally distributed among Malaysian states. Hence, this warrants an investigation into why some states have larger FIRP than others. The purpose of this paper is to investigate the pattern and determinants of FIRP in Malaysian states. FIRP in Malaysia has been agglomerated in the major and industrialized states (such as Kuala Lumpur, Selangor, Pulau Pinang and Johor). Using a panel of 14 Malaysian states over a period of 7 years (2004–2010) and applying the system Generalized Method of Moments (GMM) approach, the statistical results show that tourism agglomeration (learning about the host location), well-being of the local people, foreign investments in other sectors, religious diversity and minimum property purchase price are important determinants of FIRP. First Publish Online: 23 Sep 2013